Reflective supervision and the strategic integrative model in social work supervision - Vîșcu, Loredana; Rad, Dana (Technium Social Sciences Journal, 2024)
Supervision in the clinical field, including social work, represents a transformative process aimed at enhancing the supervisee's personal and professional development through the acquisition of essential competencies and skills. As a cornerstone of lifelong learning, supervision facilitates continuous growth and adaptation within the professional practice. Literature on clinical supervision identifies two primary categories of models: first-generation models, rooted in psychotherapeutic traditions, and second-generation models, which build upon and expand these foundations. This study introduces a model of supervision tailored to social work, derived from the integrative supervision framework. Central to this model is the supervisee's learning process, which is supported by three key components: the supervision framework, learning factors, and a reflective process involving both supervisor and supervisee in the context of case discussions. The supervisory relationship functions as the cohesive element that binds the model's components. The practical applicability of this integrative supervision model has been validated within the context of an integrative psychotherapy training program, where social workers were effectively trained and supervised. This model highlights the potential for enhanced learning outcomes and professional competency development in social work supervision.